Curriculum reform and language pedagogy: Rethinking policy and practice in Indonesia - Haryo Aji Pambudi; Hilma Oktaviana Fajrin (Graduate School, Universitas Negeri Yogyakarta, 2025)
This study aims to investigate how Indonesia’s Merdeka Curriculum reform influences English language pedagogy, focusing on the alignment between policy expectations and classroom practices. Grounded in the framework of curriculum and instructional development, the research employs a qualitative descriptive design involving document analysis, teacher interviews, and classroom observations in selected junior and senior high schools. Data were analyzed thematically to identify recurring patterns in pedagogical adaptation and implementation challenges. Validation of the instruments and data interpretation were ensured through expert judgment, triangulation, and member checking to maintain credibility and dependability. The findings reveal that while the Merdeka Curriculum encourages a significant pedagogical shift toward learner-centered, contextual, and genre-based English teaching, teachers still struggle with interpreting curriculum guidelines, designing authentic learning activities, and assessing students’ communicative competence. The analysis indicates that limited professional training and institutional support have constrained the effectiveness of the reform at the classroom level. This study concludes that successful curriculum transformation requires stronger teacher capacity-building programs, clearer instructional frameworks, and sustained policy communication between stakeholders. The research contributes to the broader discourse on curriculum reform and educational development by highlighting the interaction between national education policy and pedagogical practice in the context of a developing country.